A Computational Approach toward the Enhanced Performance of Graphene–Perovskite Schottky Solar Cells. Issue 3 (3rd December 2019) - Lin, Lingyan; Jiang, Linqin; Li, Ping; Li, Xiaoyan; Qiu, Yu
Abstract : Herein, a device modeling of graphene–perovskite Schottky junction solar cells is conducted by AFORS‐HET package. It is found that the back and front contact work function (WF) and the absorber doping concentration have important effects on cell performance. The front contact with a high WF of 5.4 eV is suggested to form the desired Schottky junction, which contributes to better efficiency. Back contact WF lower than 4.2 eV is desired to form ohmic contact. Appropriate doping concentration (10 16 cm −3 ) of perovskite favors the efficiency improvement. Under the optimal conditions, the graphene–perovskite Schottky solar cells can obtain a conversion efficiency up to 21.13%, but at a lower cost and much simpler structure comparable with the planar heterojunction perovskite solar cells. These results can provide guidance for further performance improvement of perovskite‐based Schottky solar cells. Abstract : The simulation results indicate that the front contact with a high work function (WF) of 5.4 eV is suggested to form a desired Schottky junction, whereas back contact WF lower than 4.2 eV is desired to form ohmic contact. Absorber doping concentration of 10 16 cm −3 favors the efficiency improvement. Under optimized conditions, efficiency up to 21.13% can be obtained.